Peran Remaja Masjid Nurul Iman dalam Membentuk Karakter Religius Remaja di Nagari Koto Gadang - Ulfah, Oktriyeni; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2025)
This study is motivated by the active involvement of youth members at Nurul Iman Mosque in various religious activities, despite the persistence of behaviors among some adolescents that do not reflect strong religious character, such as infrequent attendance at congregational prayers, inconsistent participation in religious studies, and a lack of respect toward elders. The purpose of this research is to understand the role of the Nurul Iman Mosque Youth Group in shaping the religious character of adolescents in Nagari Koto Gadang. A qualitative approach with a phenomenological design was used, involving 30 adolescent participants. Data were collected through in-depth interviews and validated using data triangulation techniques. The findings show that the Nurul Iman Mosque Youth Group plays a significant role in fostering religious character among adolescents through religious activities such as reciting the Quran with proper tajwid, tahsin sessions, tahlil, yasin recitations, and short-term Islamic boarding school programs (pesantren kilat). These activities strengthen spiritual connections with Allah SWT and enhance religious awareness among youth. The conclusion of this study is that mosque youth organizations contribute meaningfully to cultivating and reinforcing religious character through systematic spiritual development. The implications of this research emphasize the need to optimize the role of youth religious organizations in character formation and to develop more consistent and inclusive religious programs for adolescents within the mosque community.